Ant eating behavior - Rumalolas, Nuryanti; Tiblola, Zali Natalia; Krey, Keliopas; Dwiranti, Febriza (Inornatus: Biology Education Journal, 2022)
This study aims to determine the eating behavior of ants in the context of maintaining decomposer organisms in the ecosystem. The study was conducted using the Scan sampling method, namely recording the behavior of more than one individual per a predetermined time, which is every 10 minutes for 1 hour. The feeding behavior of ants was recorded using the Instantaneous sampling method. The results showed that ants have different eating behavior when consuming liquid and solid textured food. When eating liquid food, ants will make a neat formation, whereas when consuming solid food ants do not form formations.